Optimization of IoT services deployment in Cloud-Fog system - Đặng, Văn Đô (2021)
Our main objective, in this thesis, is to propose a solution that solve the optimal deployment of IoT services in Cloud-Fog system. The achieved results as follows: A mathematical model that represents the IoT services and Cloud-Fog system was built. - We have proposed a Mixed Integer Linear Programming model for minimizing energy consumption of system while maintaining the resource requirements and QoS constraints of IoT services. - We have designed two algorithms to efficiently deploy IoT services onto Cloud-Fog system. - We have implemented simulation scenarios to present experiment results of our proposed algorithms and compare it with the existing solutions.